PROSPECTS FOR THE DEVELOPMENT OF FINTECH TECHNOLOGIES IN THE GLOBAL MARKET OF FINANCIAL AND INVESTMENT SERVICES - Smahlo , O. V. (The actual problems of regional economy development, 2024)
The article examines the main factors contributing to the development of financial technologies in the field of the global market. The best experience of the operation of the financial technology market was analyzed and the key trends of its development were determined, namely: a high global level of implementation of financial technologies, dynamic growth of investments in fintech, the most popular investment sectors are money transfers and payments, alternative lending, cyber security, blockchain and cryptocurrency, insurance technologies. The purpose is the peculiarities, risks and prospects of the development of the FinTech industry, due to the global development of the digital economy in the world and in Ukraine. To achieve the goal, it is necessary to solve the following tasks: consider the history of FinTech development, give concepts and classification; list the main areas of FinTech activity; analyze the state of the FinTech industry in Ukraine; to study the peculiarities of regulation of the FinTech industry in the global market; consider the prospects for the development of FinTech technologies. The object of the study is the FinTech market in the world and in Ukraine. The subject of the research is a set of economic relations that arise in the process of functioning of the FinTech market. The main methods of financial technologies are: - adaptation of the legislative framework for the use of the latest IT technologies; - introducing amendments to the legislation regarding the establishment of single unified formats and a single unified form of electronic documents for the purpose of organizing electronic document flow between financial institutions; - support for the possibility of implementation - introduction of a mechanism to control the quality of such data; - centralization of IT solutions, where appropriate, to improve manageability, - data quality and cost reduction; - ensuring control over the implementation of relevant IT security standards by participants in the financial sector. The scientific novelty of the obtained results is an extremely important component of the financial system of the state, the coherence and success of the functioning of the global financial market depends on the efficiency of the organization and its level of development. The practical meaning acts as a connecting link, which is designed to ensure the redistribution of financial resources and provide financial flows with a reliable movement vector. The presence of a developed and well-organized market of financial and investment services allows capital to quickly find the most profitable areas of its application..